A informática e os contratos na atividade empresarial e seus reflexos no meio ambiente - Barbosa, André Luiz (2020)
The present scientific research aims to draw a parallel between the company and the contract itself, especially its great impact due to technological advances, mainly in information technology, in the environment, in this context. To this end, work begins with a historical concept, exposing the Industrial Revolution and its important function from the Acts of Commerce to the Theory of the Company. The Acts of Commerce propose the activity of the trader, but soon with the Industrial Revolution and with an exponential growth in economic and technological activity, several other forms of work were created and, among them, the provision of services, then the Company Theory emerged. . In sequence, we have in the formation of contracts as a subsidy to the company, its historical evolution, reinforcing the theory of natural and real obligations and their transmissions as support for entrepreneurship. In terms of the characteristics of the contracts, we had the positivity of the consumption relationship in counterpoint to the challenges expected by the company in the legal sphere, as the company had to adapt to the consumer relationship. Regarding the classification and characteristics of the main contracts, we highlight the provision of services and in this specificity the contract for the development of computer systems, their reflexes for the transfer of technology, commercialization of computer programs and mobile applications and the contract “smart contract” as a way of establishing business relationships. Therefore, it was possible to create the link between the contract and sustainability through the digital signature pact, the importance of imposing sustainable situations in business relations and artificial intelligence such as contract production and analysis. Due to the problems faced by the use of information technology and technology in general, it was necessary to create alternatives for solutions due to the impact on the environment, simply because of the unbridled use of information technology, with the need to produce energy through the use of various devices, disposal of electronics , recycling of technology products as a means of new business and technological production that does not degrade the environment. In the end, we have the company's social function as a counterpoint to the sustainable issue and how technology, contracts and information technology could help in this balance of relationships. Even with all these points listed above, we will have the opportunity by reading this research to learn about the Company, Technology with regard to computing and other technologies to mitigate impacts on the environment, in addition to conducting an analysis by means of social function from the company.